2018
DOI: 10.1103/physrevmaterials.2.085601
|View full text |Cite
|
Sign up to set email alerts
|

Microglobule formation and a microscopic order parameter monitoring the phase transition of aqueous poly( N -isopropylacrylamide) solution

Abstract: The coil-to-globule transition of poly(N-isopropylacrylamide) (pNIPAm) in water is generally believed to be driven by hydrophobic interaction between the isopropyl groups of its side chains. However, it is still unclear how dehydration and critical fluctuations of the polymer chains are correlated. Here, we use small-and wide-angle x-ray scattering and dielectric relaxation spectroscopy to cover a wide range of the relevant length and time scales, enabling us to grasp an overall picture of this phase transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 47 publications
5
29
0
Order By: Relevance
“…This second characteristic length scale has been attributed to the formation of PNIPAM microglobules at high concentration, which are also observable by small and wide-angle X-ray scattering (SWAXS). 78 Fitting the PNIPAM scattering intensities taken at 250 and 300 mg mL À1 to a sum of the Ornstein-Zernike and pseudo-Voight Lorentzian functions (eqn (S3) and (S4), ESI †) allows for the estimation of both blob correlation length and microglobule correlation length (Tables S5 and S6, ESI †). 67,78 These microglobules are dispersed in the matrix of polymer chains and have been hypothesized to weaken the structure of the hydration water network when the PNIPAM undergoes its thermally driven phase transition.…”
Section: Concentration Dependence Of Hydration Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…This second characteristic length scale has been attributed to the formation of PNIPAM microglobules at high concentration, which are also observable by small and wide-angle X-ray scattering (SWAXS). 78 Fitting the PNIPAM scattering intensities taken at 250 and 300 mg mL À1 to a sum of the Ornstein-Zernike and pseudo-Voight Lorentzian functions (eqn (S3) and (S4), ESI †) allows for the estimation of both blob correlation length and microglobule correlation length (Tables S5 and S6, ESI †). 67,78 These microglobules are dispersed in the matrix of polymer chains and have been hypothesized to weaken the structure of the hydration water network when the PNIPAM undergoes its thermally driven phase transition.…”
Section: Concentration Dependence Of Hydration Numbermentioning
confidence: 99%
“…78 Fitting the PNIPAM scattering intensities taken at 250 and 300 mg mL À1 to a sum of the Ornstein-Zernike and pseudo-Voight Lorentzian functions (eqn (S3) and (S4), ESI †) allows for the estimation of both blob correlation length and microglobule correlation length (Tables S5 and S6, ESI †). 67,78 These microglobules are dispersed in the matrix of polymer chains and have been hypothesized to weaken the structure of the hydration water network when the PNIPAM undergoes its thermally driven phase transition. 78,79 The appearance of these microglobules at high concentration even below the PNIPAM LCST may explain the trend in hydration number.…”
Section: Concentration Dependence Of Hydration Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…The Flory–Huggins solution theory describes the transformation from a favored interaction of polymer with solvent to a state where polymer–solvent interactions are unfavorable and, thus, polymer–polymer interactions increase. , On the macromolecular level, the phase transition can be described by a solution of well-solvated polymer coils below the LCST and a dispersion of (aggregated) globules above the LCST under bad solvent conditions. This coil-to-globule transition was predicted by the theories of Flory in the middle of the past century and since then was described by various groups. , Coil-to-globule transitions were studied and reported for many polymers including polystyrene, poly­(methyl methacrylate), and poly- N -acrylamides. Researchers put a lot of effort in the investigation of the phase transition process, such as the observation of the phase transition process from a single polymer chain, the detection of microglobule formation close to the cloud point, and the phase transition mechanism with respect to the water–polymer interaction. Furthermore, it was shown that the thermoresponsive behavior of polymers can be influenced by side groups introduced to the polymer by copolymerization. This can be used, for example, to control whether polymers possess LCST- or UCST-like behavior. , …”
Section: Introductionmentioning
confidence: 95%
“…To obtain information on the polymer structure at the nanoscale level, techniques such as small-angle neutron or X-ray scattering (SANS, SAXS) are typically required. By using SAXS, Yanase et al have recently shown that semidilute PNIPAM solutions feature microglobules already far below the transition temperature . This example demonstrates how complex solution structures of polymers under different solvent conditions can be and that the phase transition behavior can be complex, involving phenomena on different length scales.…”
Section: Introductionmentioning
confidence: 99%